Effects of Acute Eccentric Contractions on Rat Ankle Joint Stiffness - Eisuke, Ochi (Asist Group, 2007)
The sensation of joint stiffness is frequently observed after eccentric contractions (ECs) in human, but the joint stiffness of animals after ECs has not been examined previously. This study tested whether a bout of ECs affects rat ankle joint stiffness. We also evaluate muscle passive tension in the rat hindlimb to examine the relationships of ankle joint stiffness with muscle passive tension. Anesthetized male Wistar rats (n = 23) were firmly secured on a platform in the prone position. A bout of ECs was performed on the gastrocnemius muscle with a combination of electrically induced tetanic contractions via a skin electrode and simultaneous forced dorsiflexion of the ankle joint (velocity, 15°/s; from 0°to 45°). Passive resistive torque (PRT) of the ankle joint was measured to evaluate joint stiffness. Passive tension of the exposed gastrocnemius muscle was also measured when the maximum value of joint stiffness was obtained. The PRT on days 2, 3, and 4 was significantly higher than the pre-treatment value (days 2 and 4; p < 0.001, days 3; p < 0.01). The passive tension on day 4 was significantly higher than that of the sham-operated group. The muscle wet mass was identical in both groups, suggesting the absence of edema. We conclude PRT increases after ECs in rat ankle joint. We also show the possibility that it is associated with muscle passive tension, independent of edema formation.